Taksonomi Bloom sebagai Landasan Desain Pembelajaran Berbasis Kompetensi dalam Pendidikan Agama Islam - Irma Suriani; Khairunnisa Sakinah; Gusmaneli, Gusmaneli (CV. ITTC INDONESIA, 2025)
Bloom's Taxonomy is a conceptual framework that serves as a fundamental basis for developing competency-based learning, especially in the field of Islamic Religious Education. By applying this framework, the learning process can be structured to maximize the development of cognitive, affective, and psychomotor competencies in students. In this article, we describe how Bloom's Taxonomy can be used as the main foundation in designing effective and measurable learning to achieve holistic religious education goals. Through this approach, it is hoped that students will not only be able to understand theoretical concepts but also apply religious values in their daily activities.